Breakage Monitoring of Executive Body Cutters in Continuous Miner According to Mechanical Vibration Parameters. Part 2. Methodology for Creating a System for Mobile Monitoring of Cutter Breakages According to the Parameters of Mechanical Vibrations of the Gearbox with Natural Frequency - V. K. Sheleg; A. S. Romanovich; I. A. Konopliani (Наука и техника)
The development of research in the field of creating a mobile monitoring system for diagnosing the technical condition of mining equipment in terms of mechanical vibration parameters is one of the most science-intensive areas. The paper presents the results of investigations on the possibility of isolating the mechanical vibrations of the handles with a natural frequency  of 5 Hz, which occur with a greater or lesser amplitude in almost all registered spectra, arising from breakages  of cutters on the cutting discs of double-flow drives of the executive body of a mining machine. Therefore, it can be used for operational mobile monitoring of breakages in the cutters of the executive bodies of mining machines. An analysis of vibrations has confirmed the fact that they are transmitted to almost all non-rotating parts of the combine, where they can be registered, which allows them to be used for mobile automated monitoring of cutter breakages on cutting discs. On the example of the combine “Universal-600” it has been found that the most convenient when registering these vibrations from the standpoint of the absence of the need to introduce a signal transmission module from the rotating parts of the combine into the measuring path can be considered the placement of a vibration sensor on the body of the input gearbox of the executive body drive with its orientation in the direction combine movements, where oscillations with a frequency of  5 Hz are prevalent and it is quite simple to isolate them from the low-frequency range using standardized low-frequency one-third octave filters. The paper proposes a technique for creating a system for automated mobile monitoring of cutter breakages based on the parameters of mechanical vibrations of cutting discs with natural frequency.